PENGARUH MANAJEMEN RISIKO SEBAGAI VARIABEL MODERASI KINERJA SOSIAL, GOOD CORPORATE GOVERNANCE, DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021 – 2023 - Bianca, Sullicyanna Luna; Bayangkara, IBK (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the effect of social performance, good corporate governance, and capital structure on financial performance as well as the effect of risk management as a moderating variable in mining companies listed on the Indonesia Stock Exchange for the period 2021 - 2023. The research method used is descriptive quantitative with the research object of mining companies in the mineral and other metal sub-sectors listed on the Indonesia Stock Exchange in 2021-2023. The type of data used is secondary data in the form of annual reports and sustainability reports obtained from the company's official website and the Indonesia Stock Exchange’s website. A total of 9 companies were sampled in this study. The data obtained was then processed using Smart-PLS 2.0 software. The results of this study indicate that social performance has a negative and significant effect on financial performance, good corporate governance has a negative and insignificant effect on financial performance, capital structure has a negative and insignificant effect on financial performance, moderation of risk management strengthens the effect of social performance on financial performance but is not significant, and overall social performance, good corporate governance, and capital structure have a moderate influence tends to be small on financial performance.